Defining CO 2 and O 2 syndromes of marine biomes in the Anthropocene - Shannon G. Klein; Alexandra Steckbauer; Carlos M. Duarte (Global Change Biology, 2020)
Research efforts have intensified to foresee the prospects for marine biomes under climate change and anthropogenic drivers over varying temporal and spatial scales. Parallel with these efforts is the utilization of terminology, such as ‘ocean acidification’ (OA) and ‘ocean deoxygenation’ (OD), that can foster rapid comprehension of complex processes driving carbon dioxide (CO 2 ) and oxygen (O 2 ) concentrations in the global ocean and thus, are now widely used in discussions within and beyond academia. However, common usage of the terms ‘acidification’ and ‘deoxygenation’ alone are subjective and, without adequate contextualization, have the potential to mislead inferences over drivers that may ultimately shape the future state of marine ecosystems. Here we clarify the usage of the terms OA and OD as global, climate change‐driven processes and discuss the various attributes of elevated CO 2 and reduced O 2 syndromes common to coastal ecosystems. We support the use of the existing terms ‘coastal acidification’ and ‘coastal deoxygenation’ because they help differentiate the sometimes rapid and extreme nature of CO 2 and O 2 syndromes in coastal ecosystems from the global, climate change‐driven processes of OA and OD. Given the complexity and breadth of the processes involved in altering CO 2 and O 2 concentrations across marine ecosystems, we provide a workflow to enable contextualization and clarification of the usage of existing terms and highlight the close link between these two gases across spatial and temporal scales in the ocean. These distinctions are crucial to guide effective communication of research within the scientific community and guide policymakers responsible for intervening on the drivers to secure desirable future ocean states.